Revisiting high-frequency oscillatory ventilation in vitro and in silico in neonatal conductive airways. (June 2019) - Bauer, Katrin; Nof, Eliram; Sznitman, Josué
Abstract: Background: High frequency oscillatory ventilation is often used for lung support in premature neonates suffering from respiratory distress syndrome. Despite its broad use in neonatal intensive care units, there are to date no accepted protocols for the choice of appropriate ventilation parameter settings. In this context, the underlying mass transport mechanisms are still not fully understood. Methods: We revisit the question of flow phenomena under conventional mechanical ventilation and high frequency oscillatory ventilation in an anatomically-inspired model of neonatal conductive airways spanning the first few airway generations. We first perform at true scale in vitro particle image velocimetry measurements of respiratory flow patterns. Next, we explore in silico convective mass transport in computational fluid dynamics simulations by implementing Lagrangian tracking of tracer boli, where the ventilatory flow rate is fixed. Findings: Particle image velocimetry measurements at eight representative phase angles of a breathing cycle reveal similar flow patterns at peak velocity and during deceleration phases for conventional mechanical ventilation and high frequency oscillatory ventilation. Characteristic differences occur during the acceleration and flow reversal phases. Net displacements of the tracer particles rapidly reach asymptotic behaviour over cumulative breathing cycles and suggest a linear relation between tidal volume and convective mass transport. Interpretation: The linear relation observed suggests that differences in flow characteristics between conventional mechanical ventilation and high frequency oscillatory ventilation conditions do not substantially influence convective mass transport mechanisms. Lower tidal volumes thus cannot be compensated straightforwardly by selecting higher frequencies to maintain similar ventilation efficiencies. Highlights: First study on flow phenomena in neonatal airways under High Frequency Ventilation. Convective transport between Conventional and High Frequency Ventilation is vastly similar. Low tidal volumes at high frequencies must be carefully chosen to ensure sufficient ventilation.